EFFECT OF GIBBERELLINE (GA3) TO GROWTH AND YIELD OF CHERRY TOMATO IN HYDROPONICS SYSTEM - Saputra, Rio; Budi, Setia; Susana, Rini (Jurnal Sains Mahasiswa Pertanian, 2019)
Rio Saputra (1), Setia Budi (2), Rini Susana (3)(1) Student at the faculty of Agriculture, Tanjungpura University(2) Lecturers at the Faculty of Agriculture, Tanjungpura Universitye-mail : riosaputragalimg@gmail.com ABSTRACT             The researcs aims to determine the effect of gibberellin (GA3) and obtain the best concentration of gibberellin (GA3) on the growth and yield of cherry tomato with hydroponics system. The research was conducted on Jl. Reformasi. Mathematics, Pontianak West Kalimantan. This researc conducted from 14th December 2017 to 22nd March 2018. The experimental design used in this study was a Completely Randomized Design (CRD) consist of 5 treatment levels each treatment 3 plants,  replicate 5 times so the total 75 plants. The treatment namely g0 = No gibberellin (GA3) g1 = 5 ppm GA3 (50 ppm Gibgro), g2 = 10 ppm GA3 (100 ppm Gibgro), g3 = 15 ppm GA3 (150 ppm Gibgro), g4 = 20 ppm GA3 (200 ppm Gibgro. The variables observed in this study include plant height (cm), number of productive branches (branch), dry weight of plants (g), number of fruits per plant (fruit), fruit weight per plant (g), weight per fruit (g), percentage of harvesting fruit (%). Supporting variables including temperature (0c), humidity (%). The researcs showed that gibberellin significantly affected the dry weight of the plant, the number of fruits per plant and the percentage of finished fruit. The concentration of giberelin (GA3) 5 ppm equivalent (50 ppm Gibgro) is efficient concentration for the growth and yield of cherry tomatoes in hydroponic systems. Keywords: Cherry Tomato, Gibberellin, Hydroponic